Role of linguistic strategy in health public administration reform: Implications for service quality - Mustaking Mustaking; Novalia Tanasy (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Linguistic strategy has emerged as a critical yet underexplored determinant of health service quality within public administration systems. Ineffective policy language, inconsistent terminology, and a lack of cultural alignment often create barriers to service access and utilization. This study aimed to examine the role of linguistic strategies in shaping health service quality and quantify their impact across key service dimensions. Research Methodology: An explanatory sequential mixed-methods design was employed, combining a cross-sectional survey (n = 422) with qualitative inquiry. Participants included health administrators, frontline workers, and service users in South Sulawesi, Indonesia. Data were collected using validated questionnaires and analyzed using descriptive statistics, chi-square tests, and multivariate regression models. Statistical significance was set at α = 0.05. Results: Linguistic strategy dimensions were significantly associated with service quality outcomes. Cultural appropriateness showed the strongest effect (β = 0.35; 95% CI: 0.24–0.46; p < 0.001), followed by clarity of communication (β = 0.32; 95% CI: 0.21–0.43; p < 0.001) and terminology consistency (β = 0.27; 95% CI: 0.16–0.38; p < 0.001). Feedback mechanisms also demonstrated a significant contribution (β = 0.22; 95% CI: 0.11–0.33; p = 0.002). Demographic variables had a limited influence. Conclusion: Linguistic strategy is a decisive and modifiable determinant of health service quality. Integrating clear, consistent, and culturally adaptive communication into health administration reform can substantially improve accessibility, responsiveness, and user satisfaction. Policy interventions should prioritize standardized terminology, simplified policy discourse, and strengthened feedback systems to enhance overall system performance.